Ars Docendi et Scribendi: Essays in honour of Johan Scott - Edited by the Faculty of Law, University of Pretoria
Festschrift - a collection of articles by the colleagues, former students, etc. of a noted scholar, published in his or her honour. During his travels abroad Johan Scott built up a wide network of international scholars who over time became a valued circle of friends, many of whom spent enriching moments in his company and who contributed to this Festschrift. Contributors were requested to write in their home language, and furthermore to submit their contributions for publication in other journals worldwide, specifically accrediting this Festschrift in order to expand access worldwide to the wonderful contributions written in honour of our colleague. Great scholars like Johan never retire. They might go fishing more than they could in the past, but his calling of being a true teacher will never fade. Scholars like Johan understand that the present and the future are inevitably linked to the past, and although education depends on talent and performance, it should always serve to build character and a vision for future generations.